Valorizing sardine scales: a circular approach to sustainable collagen for cosmetics and nutrition applications - Santos Filipe, Marcia; André, Rebeca; Ferreira, Marco; Diaz-Lanza, Ana María; André, Vânia; Alves, Marta M.; Pacheco, Rita; Rijo, Patrícia (Frontiers in Pharmacology, 2024)
Background and Objective In recent years, the consumption of fish products has led to a worrying trend where approximately two-thirds of the total amount of fish is discarded as waste. At the same time, scientific interest in exploring natural collagen sources for cosmetics and dietary supplements has increased. This study explores the potential of valorizing sardine scales (Sardina pilchardus), a by-product of the canning industry, through the extraction of collagen for potential use in dermocosmetic formulations and food supplements. Methods Collagen from sardine scales was obtained though acid and enzymatic extraction. The collagen extracts were characterized by UV-Vis, FTIR spectroscopy, SDS-PAGE, powder X-ray diffraction (PXRD) and scanning electron microscopy (SEM). The collagen was hydrolysed with papain to small peptides. Subsequently, the biological activities of acid-soluble collagen as well as the collagen peptides in terms of antioxidant and antimicrobial activity were evaluated. Furthermore, the capacity of collagen peptides to permeate the intestinal barrier, simulated with caco-2 cells, was evaluated. Results Purified collagen extracts were obtained from sardine scales, with enzymatic extraction method having a yield three times higher than the acid method. The SDS-PAGE analysis confirmed the extraction of type I collagen as well as its hydrolysis into small fragments (25–12 kDa). In terms of biological activities, collagen and collagen peptides have not demonstrated antimicrobial activity. However, regarding antioxidant activity, collagen peptides showed three times more capacity compared to non-hydrolyzed collagen. Meanwhile, in 6 h, about 6.37% of collagen peptides could permeate the intestinal barrier. Conclusion This work represents a continuous effort to advance our understanding and utilization of Portuguese marine waste resources, with focus on the valorization of sardine co-products for the development of food supplement or cosmetic formulations, contributing to the sustainable evolution of the circular blue economy.